Analysis of Early Childhood Education Management in Improving the Quality of Early Childhood Education at TK Darul Fallah 3 Samarinda - Rahmawati, Indah Kurnia; Saputri, Pradiva Mei; Habibah, Zahra Nur; Putri, Neyla Restyana; Dwiyanti, Sharena Diva; Sjamsir, Hasbi; Rozie, Fachrul (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
Early Childhood Education (PAUD) constitutes an essential foundation for shaping children’s character, attitudes, and basic abilities before they enter the next educational level. At this age, appropriate stimulation significantly influences their growth and development. Therefore, PAUD institutions play a strategic role in providing a learning environment that is conducive, enjoyable, and aligned with children’s developmental needs. To understand how PAUD institutions carry out their role, we employed a direct field observation method. Through observation, we gathered information regarding the organizational structure, curriculum used, facilities, resource management, and forms of parental involvement in supporting the children’s educational process. This observation was conducted at TK Darul Falah 3, a PAUD institution located in Samarinda city. This institution holds a vision and mission to form participants who are devoted, intelligent, cheerful, and environmentally conscious. By conducting this observation, the students (researchers) gained an understanding of how the institution executes learning activities and school management to optimally support the children’s growth and development.